"Nuevos" Lenguajes Audiovisuales: Algunos Criterios para Su Evaluación - Araos Uribe, Carlos (Re-presentaciones: Periodismo, comunicación y sociedad, 2008)
The article concentrates in the clarification of the new audiovisual language concept, exploring the consequences that this will have in a true and effective form to evaluate and to develop this aspect in the consequences formation of the communicators.